Exploring the Teacher’s Experiences of Using Digital Technology in Teaching Writing Skills - Benyta, Bunga Elsa; Ningsih, Sri Kusuma (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
In recent years, technology has been increasingly used in teaching in schools. Teachers and students use digital technology to make teaching-learning more effective and enjoyable. This situation has been supported by policies from schools that require teachers to use digital technology in teaching. This study's survey findings indicate that teachers already use digital technology in teaching, which can make students interested in learning English. This study also relates to the teacher's attitude toward learning writing skills using digital technology. This study employed interviews conducted by four English teachers at a school that mostly uses digital technology in teaching writing skills. These teachers affirm that digital technology can make teaching more accessible and make students interested in learning English.